Some Extractions of Fixed Point Theorems Using Various E.A Properties - Vijayabaskerreddy, Bonuga; Srinivas, Veladi (Communications in Mathematics and Applications, 2021)
This paper deals with some fixed point theorems using the notions of E.A property, common E.A property, E.A like property and common E.A like property along with weakly compatible mappings. Additionally, some examples are also discussed to describe the various E.A properties.
Keywords: Common fixed point; Weakly compatible mappings; E.A property; Common E.A property; E.A like property; Common E.A like property